The influence of media in the digital democracy in Indonesia - sabarofek, luis armando; Rahmawati, Dian Eka (Jurnal Studi Komunikasi, 2026)
This study examines how digital media reshape democratic quality in Indonesia by transforming information flows, public opinion formation, civic participation, and government accountability within the digital public sphere. Rather than treating these dimensions separately, this research adopted the concept of democratic quality to capture the broader systemic impact of digital communication on contemporary democracy. This study combined bibliometric and qualitative approaches to provide both a macro-level mapping and an in-depth thematic interpretation. Bibliometric data were collected from the Scopus database covering the period 2020–2025, using PRISMA procedures, resulting in 56 core publications. VOSviewer was used to identify research clusters and intellectual trends, while NVivo 12 Plus supported qualitative thematic analysis. The findings indicate a dominant shift in global research from early concerns with digital participation and public engagement toward growing attention to algorithmic power, disinformation, polarisation, and platform governance. In the Indonesian context, digital media simultaneously expands democratic inclusion through increased participation and transparency, while also weakening deliberative quality due to misinformation, echo chambers, and low digital literacy. This study highlights that platform algorithms and information governance increasingly shape the trajectory of digital democracy. This research contributes to communication studies by offering an integrated framework for understanding how digital media restructure democratic quality in the evolving digital public sphere.